Measurement of GSH, SOD and MDA some Antioxidant level after Excises Athletes - Harith Abdelelah Alshukri 1 , Mazin Hadi Kzar 2 , Aied Kareem Abdaun3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Antioxidants are a line of defense that protects the cells of the body. Attacking the stray oxygen molecules.The function of these antioxidant is to add a group of electrons to the blood vessels to give them toelectrolytes or monovalent free radicals so that they stabilize and calm down and do not destroy cells. Thus,antioxidants work to achieve a balance between free radicals and antioxidants In the cell and keeps the cellfrom being damaged. Increased electrolytes or free radicals work To weaken the ability of antioxidants’ andenzymes secreted by cells despite the fact that the cell has a self-protection and a defensive line to secreteself-antioxidants, and here the importance of antioxidants arises. These metabolic changes increase theoxidative effort and affect the ability to achieve and the efficiency of athletes, as well as the body containsa lot of antioxidant systems Oxidative stress that includes enzymes such as GSH) Glutathione Dos) Superoxide D ismutses. Exercise can produce an imbalance between ROS and antioxidants, which is referredto as oxidative stress. Dietary antioxidant supplements are marketed to and used by athletes as a meansto counteract the oxidative stress of exercise. Whether strenuous exercise does, in fact, increase the needfor additional antioxidants in the diet is not clear. This research showed the role of free radicals in causingoxidative stress during exercise. The results showed significant increased in malondialdehyde (MDA) level(as an index of lipid peroxidation) glutathione (GSH) superoxide dismuatse activity (SOD) in subjects afterefforts of exercise in comparison with the control group.